Kaj (vse oziroma vsaj) bi morali vedeti uporabniki o informacijskem sistemu e-ZK - Trklja, Jasminka Jaša (Podjetje in delo, 2013)
Article presents the information system e-ZK (e-ZK is electronic Land Registry of the Republic of Slovenia and e-ZK web portal is an integral part of it) and the major responsibilities of the Center for Informatics of the Supreme Court of the Republic of Slovenia and Working Group for Land Registry Information system (iZK) in the Registry Department of the Supreme Court.
Keywords: elektronsko poslovanje; informacijski sistemi; Slovenia; Slovenija; sodišča; zemljiške knjige